Study Of Traditional Food At Maminang Events In Lubuk Minturun Sub-District, Padang City - Rahmi, Zulfiandra; Gusnita, Wiwik; Holinesti, Rahmi; Siregar, Juliana (Universitas Negeri Padang, 2024)
This research is motivated by the lack of knowledge of the younger generation about customs, one of which is food at maminang events. This research aims to describe the stages, types of traditional food, ways of processing traditional food, tools used to process and serve traditional food and the meaning of the food served. at a traditional Maminang event in Lubuk Minturun Village, Padang City. The type of research used is qualitative research, the research object is traditional food at the maminang event in Lubuk Miturun Village, Padang City, the research informants are Ninik Mamak, Bundo Kanduang, and women in Lubuk Minturun Village who know about the maminang event. The data collection techniques in this research are observation, interviews, and documentation and the data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this research illustrate that the stages of carrying out traditional Maminang events are divided into two, namely: preparation before the traditional Maminang event includes batanyo/bakandak pie and processing traditional food, and stages of traditional Maminang events include going to the man's house, handing over luggage, sit down and eat basamo, barundiang or maetong hari/manakok hari, batuka tando and go home. The traditional food served at the Maminang event is nasi lamak, chicken singgang, sponge cake, bananas and jelly. The tools used to process traditional food at the Maminang event are the steamer, cauldron, talenang, pariuk, stove and plastic spoon. The tools used to serve and carry traditional dishes are carano, tray, pinggan gadang, tray, and piriang. The food served has deep meaning and purpose.